Bridging disciplines-key to success when implementing planetary health in medical training curricula - Ebba Malmqvist; Anna Oudin; Anna Oudin (Frontiers Media S.A., 2024)
Planetary health is being or should be added to medical training curricula in accordance with association consensus. Several articles published in recent years have addressed concern on the implementation, and the challenges that can occur if not addressed properly. This scoping narrative literature review focuses on planetary health as a concept, as well as challenges and suggested solutions to address these challenges. Planetary health is an important concept and needs to be addressed in all medical training. We found that one main challenge is implementation without ensuring the right competences and resources. Medically trained teachers set out to understand and teach complex natural and social systems. At some institutions the time allocated to teach planetary health is limited or non-existent. Case studies and student led teaching are solutions suggested, while other argue that true interdisciplinarity by inviting experts are more in line with what we expect from other subjects. In conclusion, the roots of planetary health, the enormous health risks at stake and nature of the subject requires medical training to adopt a true inter/trans-disciplinary approach to succeed. It might not be expected for all students to become planetary health experts, but all need a general understanding of the most important aspects and values.